IMPROVING UNDERSTANDING OF GENETIC SUBSTANCES THROUGH GUIDED DISCOVERY LEARNING METHODS - Evi Zunaidah (ScienceEdu, 2021)
This study aims to improve student learning outcomes on genetic substances by applying the Guided Discovery Learning Method. The subjects of this study were students of class XII MIPA 1 who collected 40 students. This research is a Classroom Action Research (CAR) which consists of two cycles, and each process includes the planning, implementation, and reflection stages. The data collection techniques are test techniques, observations, and field notes. The data analysis technique used is reflective, meaning that it is always reflected in the learning process. The research result is that the Guided Discovery learning method can improve student learning outcomes in understanding genetic material.